Pengaruh Ion Na+, Ion Hg2+ dan Ion Cr3+ Terhadap Kinerja Sensor Potensiometri Ion Timbal (II) Tipe Kawat Terlapis Berbasis Pirofilit - Qanitah Fardiyah; Barlah Berlianti; Ika Rosemiyani (Jurnal Kimia Valensi, 2015)
Generally ionophores  (active materials) in a potentiometric is derived from organic compounds. In this research used ionophores derived from ainorganic compounds that pyrophyllite. Potentiometric sensors lead (II) ions based on pyrophyllite as ionofor has been developed. The electrode had  polyvinilchloride (PVC) as polymer matrix and dioctylpthalate (DOP) as plasticizer. It showed a good Nernstian slope of 29.33 mV/decade, a lead linear range concentration between 10-1- 10-5 M, and detection limit of 8.054 x10-6 M  (equal with 1.669 ppm of lead). By using the electrode, the objectives of this research were to investigate the effect of interfering ions  Na+, ion Hg2+ and ion Cr3+ to the performance of the potentiometric sensors lead(II) ion based pyrophyllite coated wire type. The selective coefficients (kij) were determined using the mix solution methode  at  10-3 M of interfering ion. The result showed that the potentiometric sensors lead(II) ions based  on pyrophyllite coated wire type could be used optimally at  pH 5. The potentiometric sensors lead(II) ion based pyrophyllite coated wire type showed a good selectivity for interfering ions (Na+, Hg2+, dan Cr3+) and showed no interference to the performance of the potentiometric sensors lead (II) ion based pyrophyllite coated wire type with selectivity order of Pb2+> Hg2+> Cr3+> Na+. DOI :http://dx.doi.org/10.15408/jkv.v0i0.3144